Cost-Effectiveness Evaluation of Bariatric Surgery for Morbidly Obese with Diabetes Patients in Thailand. (3rd February 2019) - Viratanapanu, Ithiphon; Romyen, Chavalit; Chaivanijchaya, Komol; Sornphiphatphong, Sikarin; Kattipatanapong, Worawit; Techagumpuch, Ajjana; Kitisin, Krit; Pungpapong, Suppa-ut; Tharavej, Chadin; Navicharern, Patpong; Boonchayaanant, Patchaya; Udomsawaengsup, Suthep
Abstract : Background . Bariatric surgery is a choice for treatment in morbidly obese patients with type 2 diabetes mellitus (DM type 2) who have inadequate diabetes control with only medical treatment. However, bariatric surgery requires highly sophisticated equipment, and thus the cost of surgery seems to be very high following the procedure compared with the cost of conventional diabetes care. This raises the question of whether bariatric surgery is cost-effective for morbidly obese people with diabetes in Thailand. Objective . To perform a cost-effectiveness evaluation of bariatric surgery compared with ordinary treatment for diabetes control in morbidly obese DM type 2 patients in Thailand. Methods . Cost-effectiveness study was conducted, using a combination of decision tree and Markov model in analysis. Treatment outcomes and healthcare costs were incurred by data from literature review and retrospective cohort in King Chulalongkorn Memorial Hospital from September 2009 to March 2016 for the conventional and bariatric surgery group, respectively. One-way sensitivity was used for analysis of the robustness of the model. Cost-effectiveness was assessed by calculating incremental cost-effectiveness ratios (ICERs). Monetary benefits at a threshold of 150, 000 to 200, 000 Thai baht (THB) per quality-adjusted life-year (QALY) based on the Thailand gross domestic products (GDP) value was regarded as cost-effectiveness of bariatric surgery. Results . Bariatric surgery significantly improves the clinical outcome including long-term diabetes remission rate, hemoglobin A1C, and body mass index (BMI). The incremental cost per QALY of bariatric surgery compared with the medication control is 26, 907.76 THB/QALY which can consider bariatric surgery as a cost-effective option. Conclusions . Use of bariatric surgery in morbidly obese with DM type 2 patients is a cost-effective strategy in Thailand's context.